Subblocks interleaving PTS technique with minimum processing time for PAPR reduction in OFDM systems. Issue 5 (11th May 2016) - Al‐Hussaini, Khalid; Ali, Borhanuddin Mohd; Varahram, Pooria; Hashim, Shaiful Jahari; Farrell, Ronan
Abstract : This study presents subblocks interleaving partial transmit sequence (SBI‐PTS) technique having low complexity for reducing the peak‐to‐average power ratio in orthogonal frequency division multiplexing systems. In this technique, a new subblocks interleaver is proposed, in which each subblock is interleaved with the others. Moreover, a new optimisation scheme is introduced, in which the number of iterations is made to be equal to the number of subblocks only which results in reduced processing time and less computation that leads to reduced complexity. Simulation results demonstrate that the new technique can effectively reduce the complexity by up to 99.95% (for subblocks number M = 16, inverse fast Fourier transform size N = 256) compared with the conventional PTS and new existing PTS techniques and yield good bit error rate performance. The other salient feature of this scheme is that it does not require side information and thus it offers increased transmission efficiency.